EVALUATION OF THE IMPACT OF STARTER CULTURE DIFFERENTIATION ON CHEESE SENSORY PROFILE - Wulandari, Afiza; Nugroho, Dimas Fajar; Imaniah, Nida'ul Husna; Falah, Fadhilah Dhani Santika (Universitas Veteran Bangun Nusantara, 2026)
This study evaluated the effect of different starter cultures on the organoleptic quality of cow’s milk cheese. Three starters — Rennet Qso (tablet), Rennet Nabati (powder), and Rennet (Khomiiratul Jibni) were tested at 1% concentration. A Completely Randomized Design with four treatments and four replications was employed. Organoleptic parameters (color, taste, aroma, texture, overall liking) were evaluated by 20 panelists using a 1–5 hedonic scale. Data was analyzed by ANOVA and Duncan’s test. The powdered Rennet Nabati treatment yielded the highest scores in texture, aroma, and overall acceptance. Thus, Rennet Nabati is recommended for artisanal cheese production. Keywords: cheese, cow’s milk, organoleptic, Rennet Nabati, starter culture.